Morphological Indicators of Positive Emotions in “Przewodnik Katolicki” in the Years 1895–2005 - Wiatrowski, Przemysław (Poznańskie Studia Slawistyczne, 2015)
The object of the linguistic analysis are articles published in the years 1895–2005 in „Przewodnik Katolicki” – one of the oldest Polish periodicals and the oldest Catholic weekly in Poland, chich to a large extent has preserved its traditional line. The research conducted in this paper is of an empirical, material and interpretative character. Its purpose is the analysis of linguistic facto excerpted from „Przewodnik Katolicki” which were used by the magazine editors to express positive emotions. Only morphological indicators of positive emotions (inflectional expressive forms, morphological expressive forms) have been analyzed. Analyzing the expressive forms, the author reveals their factual emotional values coded in the elements constituting those constructions, i.e. inflectional morphemes and morphological formants. To achieve this goal he also takes into consideration other aspects of the process of expression. He includes both interactions between the constituent elements (the inner context) of inflectional and morphological structures and the activity of other components of an utterance or consituation which jointly organize the emotional meaning of expressive forms. The reconstructed senses are presented in the form of explications, following the ideas of Anna Wierzbicka and Stanisław Grabias, as analytical formulas equivalent with the defined constructions.